Specific detection of high mobility group box 1 degradation product with a novel ELISA - Takaaki Totoki; Takashi Ito; Shingo Yamada; Goichi Honda; Tsuyoshi Hattori; Ikuro Maruyama (BMC, 2021)
Abstract Background During sepsis or sterile tissue injury, the nuclear protein high mobility group box 1 (HMGB1) can be released to the extracellular space and ultimately into systemic circulation, where it mediates systemic inflammation and remote organ failure. The proinflammatory effects of HMGB1 can be suppressed by recombinant thrombomodulin (rTM), in part through a mechanism involving thrombin-rTM-mediated degradation of HMGB1. Given that HMGB1 is proinflammatory but the HMGB1 degradation product (desHMGB1) is not, an analytical method that discriminates between these two molecules may provide a more in-depth understanding of HMGB1-induced pathogenicity as well as rTM-mediated therapeutic efficiency. Methods A peptide that has a shared amino-terminal structure with desHMGB1 was synthesized. C3H/lpr mice were immunized with the desHMGB1 peptide conjugate, and antibody-secreting hybridoma cells were developed using conventional methods. The reactivity and specificity of the antibodies were then analyzed using antigen-coated enzyme-linked immunosorbent assay (ELISA) as well as antibody-coated ELISA. Next, plasma desHMGB1 levels were examined in a cecal ligation and puncture (CLP)-induced septic mouse model treated with rTM. Results Through a series of screening steps, we obtained a monoclonal antibody that recognized desHMGB1 but did not recognize intact HMGB1. ELISA using this antibody specifically detected desHMGB1, which was significantly increased in CLP-induced septic mice treated with rTM compared with those treated with saline. Conclusions In this study, we obtained a desHMGB1-specific monoclonal antibody. ELISA using the novel monoclonal antibody may be an option for the in-depth analysis of HMGB1-induced pathogenicity as well as rTM-mediated therapeutic efficiency.